(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2021)
The COVID-19 pandemic creates new jeopardy to fundamental principles and rights at work. In the Republic of North Macedonia workers were the first to be hit after the state of emergency was declared because they had to deal with the consequences of the coronavirus. It seems that in the country workers often paid the price of lockdown measures with violations of their labour rights, whose number was increasing daily. The COVID-19 pandemic is restricting freedom of association, denying workers the right to unionize strike and engage in collective bargaining. Some laid-off workers have reported difficulties in accessing social protection schemes. Another issue is a lack of suitable protection to safeguard the rights of workers – cut down expenses, use of days off, occupational health and safety, access to benefits, and unfounded termination of the employment contract. Since the pandemic began, North Macedonian labour law does not only rely on existing regulations. The aim of this paper is to increase awareness and understanding of what lawmakers can do now to address, mitigate, and remediate labour rights concerns, with a clear focus on managing labour rights. First, the paper will try to answer the question does North Macedonian labour law have good mechanisms, if any, that protect the rights of workers in the pandemic. And second, we will analyze if the North Macedonian legislators reacted upright to the pandemic by amending several new labour laws over a short period. Both, primary and secondary sources will be used for the explanation of fundamental principles and rights at work. Furthermore, analysis will be done on the introduction of new rules and working conditions.